A educação no horizonte da transição ao socialismo: lições da lutade classes e do internacionalismo - Félix, Antônio Ferreira (2019)
Of the beings that developed on the face of planet earth, man to some extent, by distancing himself and not separating himself from nature, is located in the sphere of social being. Endowed with conscience and will can be considered the only one that by a set of objective and subjective factors aroused by the historical progress of life maintenance through work, interaction between man and nature, submits this technique to better meet their needs and mitigate their efforts. achieve a domain very close to the absolute in the production of the elements that guarantee their existence. Life, in turn, goes on like nature in a permanent process of transformation. The human world behaves like nature by acting with its social body at a time when it does not separate from its natural organic composition. With nature in motion and the human being in permanent mobility for the demands of life in a sociability divided into antagonistic, privileged and disinherited classes, we will highlight the role of education, where the uneducated can and should in certain circumstances educate the educated. In our object, we discuss the evolution of life, passing through the old, slave, feudal and capitalist modes of production and the transition to socialism via the October Revolution that took place in the Soviet Union in 1917. Our intention is to highlight the importance of education as auxiliary instrument of the working class in the struggle to overcome the exploitation of capital and its journey of transition to socialism. We emphasize based on studies of the first science, the History of humanity, in our research that education imposes itself as necessary the human condition, and, above all as a primordial element in incorporating the productive forces in revolutions and essentially in overcoming capitalism in a journey of transition to socialism when, through the clashes of the antagonistic classes, a violent education gradually interested in its connection with the wealth-producing class can become a disinterested human education in the service of development, equality and formation. human personality free from the dark ambition for individual riches. To this end, we draw on a theoretical-bibliographical research anchored in the dialectical historical materialism of the Marx and Engels school so well interpreted by Lenin, Trotsky and Rosa Luxemburg of the following works: Marx and Engels in the Capital (2013); The German Ideology (2007); Communist Manifesto (2005); Aníbal Ponce in Education and Class Fight (2007); Trotsky in the following works: History of the Russian Revolution (Tome I and II, 2007); The Theory of Permanent Revolution (2011); The Transition Program for Socialist Revolution (2008); Way of life issues. Their morals and ours (2009); Pierre Broué in History of the Communist International (Tome I and II). We highlight the class struggle, the International, the leadership crisis of the world proletariat, the permanent revolution, the transition to socialism and the role of education inserted in a transition program to overcome capitalism, demonstrating revolutions as an instrument of transformation and construction. of the new.